2021
DOI: 10.1007/s42452-021-04509-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dynamic maceration of Clausena anisata (Willd.) Hook. f. ex Benth. leaves to maximize trans-anethole content

Abstract: Trans-anethole possesses several biological and pharmacological effects. It is also used as masking agent in household products and as a flavoring agent in food. Clausena anisata (Willd.) Hook. f. ex Benth. leaves are reported as a source of trans-anethole that makes their anise-like odor. This work sought to optimize the dynamic maceration of C. anisata leaves to maximize the trans-anethole content. The circumscribed central composite experimental design was applied to investigate the effects of extraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A high estragole content will result in a low anethole content; conversely, if the anethole content is high, the estragole content will be very low [13]. Based on chemotaxonomic research, these two compounds can be found in several essential oil-producing plants, including Foeniculum vulgare (Family Apiaceae), Аrtemisia dracunculus, Clausena anisata (Family Asteraceae) and Tagetes pusilla, Pimpinella anisum (Family Apiaceae) [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…A high estragole content will result in a low anethole content; conversely, if the anethole content is high, the estragole content will be very low [13]. Based on chemotaxonomic research, these two compounds can be found in several essential oil-producing plants, including Foeniculum vulgare (Family Apiaceae), Аrtemisia dracunculus, Clausena anisata (Family Asteraceae) and Tagetes pusilla, Pimpinella anisum (Family Apiaceae) [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%